Small-sized type A thymoma with pulmonary metastasis: a case report - Sachi Kawagishi; Tomohiro Maniwa; Hirokazu Watari; Ryuhei Sakata; Akiisa Omura; Ryo Tanaka; Toru Kimura; Keiichiro Honma; Jiro Okami (Surgical Case Reports)
Abstract Background Type A thymomas comprise a homogenous population of neoplastic epithelial cells that are characterized by a spindle/oval shape without nuclear atypia. They may be accompanied by few non-neoplastic lymphocytes. Most type A thymomas are detected in the earlier Masaoka stages. Compared to other thymoma subtypes, they rarely metastasize or recur. There have been some reports of patients with type A thymomas with pulmonary metastasis; however, these thymomas were 20 mm or more in size. Herein, we report the case of a patient who underwent surgical resection for a small-sized type A thymoma (12 mm) with pulmonary metastasis. Case presentation A 62-year-old patient presented with an abnormal shadow in the left lung on plain chest radiography during a medical checkup. Chest computed tomography revealed a 12-mm tumor in the anterior mediastinum and a 13-mm nodule in the left lower lobe. 18F-fluorodeoxyglucose positron emission tomography/computed tomography revealed uptake in the anterior mediastinal tumor, but did not show a significant uptake in the pulmonary nodule. The patient underwent surgical resection on two separate occasions, and was diagnosed with an atypical type A thymoma and pulmonary metastasis. The TNM classification was p-T1aN0M1b stage IVb, and it was stage IVb according to the Masaoka staging system. No recurrence was observed during the follow-up. Conclusions We report a case of the smallest type A thymoma with pulmonary metastasis. Pulmonary metastasis secondary to a type A thymoma should be considered even if the thymoma is small in size (< 20 mm).